POTENSI PRODUKSI HIJAUAN Mikania cordata SEBAGAI PAKAN TERNAK RUMINANSIA DI PROVINSI BALI - I Wayan Suarna; Ni Nyoman Suryani (Pastura : Jurnal Ilmu Tumbuhan Pakan Ternak, 2018)
Identification of potential forage variety from various biological resources of forages has become a vital need in order to increase forage production. A study has been carried out aimed to finding out the potential forage production of Mikania cordata and its development potential as tropical forage. The research method used is a field survey of the presence of Mikania cordata in all regencies in Bali. The survey results show that the production of Mikania cordata is 840 kg ha-1 with a high water content. Mikania is very easy to spread and is very fond of shade and can grow well on non-humid land. Almost all districts in Bali can find Mikania plants. Mikania has been widely used by farmers as feed mixed with various local grasses. It was concluded that Mikania cordata is very potential as a source of forage feed, easily developed in sharing patterns of crop integration and high production. Keywords: Mikania cordata, identification, and forage production